Improving working relationships with families in German early childhood interventions home visitors: a quasi-experimental training study - Georg, Anna; Hauschild, Sophie; Schröder-Pfeifer, Paul; Kasper, Lea A.; Taubner, Svenja (BMC Psychology, 2022)
Home visitation services within German Early Childhood Interventions (ECI) for families with a child aged 0-3 are mainly provided by frontline pediatric nurses and family midwifes. Home visitors are often challenged by difficult interactions with families. Mentalizing, the ability to understand mental states of oneself and others, is a key skill for building effective working relationships, which in turn positively affect intervention outcomes. The aim of this study was to investigate if a mentalizing skills training offered to home visitors active in German ECI contributes to continued professional development. We investigated, whether the training positively affected the quality of the working relationships with families as well as home visitors’ empathy, self-efficacy, and mentalizing.
Gesehen am 25.01.2023